Yoga for Dementia : a Guide for People with Dementia, Their Families and Caregivers. - Plahay, Tania (Jessica Kingsley Publishers, 2018)
With yoga sequences, breathing exercises and meditations, this book shows care home staff and family carers how to use yoga to help people with dementia reduce the negative effects of their symptoms. The programme can be used with both individuals and groups, and can adapted for a range of abilities.